Analyzing Tokopedia X BTS ADS According to Discourse Analysis - Akita Putri Artelu (Universitas Muhammadiyah Barru, 2022)
Tokopedia introduced a boy group from South Korea named BTS as Brand Ambassador (BA). Through advertising, Tokopedia tries to attract people's attention, especially K-pop fans. This research was made to analyze the elements of communication of language, the elements of the macro functions, what maxims are obeyed, and what maxims are flouted in the Tokopedia x BTS video advertisement. This research uses the discourse analysis method. Discourse analysis is a qualitative method that concentrates more on the meaning of the data than on the generalization of the data. The results of this research are that the seven elements of communication of language are present in both Tokopedia x BTS advertising videos, while the elements of the macro functions are only fulfilled by the second video ad and the first ad video only obeys three maxims, while the second ad video has obeyed all maxims.